2019
DOI: 10.1021/acs.jpcb.9b01383
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte-Induced Collapse of a Charged Macromolecule

Abstract: In the recent surge of investigations on osmolyte-induced conformational landscape of hydrophobic macromolecules notwithstanding, there is a lack of understanding of how the presence of Coulombic charges in the macromolecule dictates its own conformational preference in aqueous media of osmolyte. Toward this end, in this work, we have computationally simulated the trimethyl amine N-oxide (TMAO)-induced collapse behavior of a charge-neutral polymer by varying the number of oppositely charged monomeric beads of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Moreover, the current work's demonstration that protein-stabilizing osmolyte may have ambivalent interactions with the proteins, can have possible implication in their mechanistic action in modulating protein-protein interactions. 29,[43][44][45] Recent experiments in these directions have shown that osmolyte and non-osmolytes may have a distinct role in perturbing charge-mediated inter-protein interactions 43 and that zwitterionic osmolytes can resurrect the electrostatic interactions among charged surfaces, with low temperature playing an important role. 44,46,47 Future investigation in the possible molecular mechanism of osmolyte-induced protein-protein interaction and its possible modulation of liquid-liquid protein phase separation 48 can provide interesting insights.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current work's demonstration that protein-stabilizing osmolyte may have ambivalent interactions with the proteins, can have possible implication in their mechanistic action in modulating protein-protein interactions. 29,[43][44][45] Recent experiments in these directions have shown that osmolyte and non-osmolytes may have a distinct role in perturbing charge-mediated inter-protein interactions 43 and that zwitterionic osmolytes can resurrect the electrostatic interactions among charged surfaces, with low temperature playing an important role. 44,46,47 Future investigation in the possible molecular mechanism of osmolyte-induced protein-protein interaction and its possible modulation of liquid-liquid protein phase separation 48 can provide interesting insights.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the idea of stabilization of hydrophobic interaction via preferential binding of TMAO with the surface, in contrast to its exclusion from the surface, has received regular attention in multiple subsequent studies. 18,[22][23][24][25][26][27][28][29] However, these works have been mostly limited to model polymer and not been validated in case of realistic proteins, until recently.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer mimics bead-in-a-spring model with a total of 32 beads connected by harmonic bonds and angles, the details of which are documented else-where. 29 The polymer consists of alternative positive and negative charges on the beads in a periodic fashion . Apart from the electrostatic interaction, the polymer beads additionally interact with each other and the aqueous media via lenard Jones (LJ) interaction.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…found in our previous work. 29 We have run 200 independent simulations, each 30 ns long, by starting with diverse conformation of the polymer.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Computational models of the three systems studied in the current work: a) 32bead model polymer, b) C-terminal domain of GB1 β-hairpin (residues 41-56) and c)Bovine pancreatic trypsin inhibitor (BPTI) protein found in our previous work 29. We have run 200 independent simulations, each 30 ns long, by starting with diverse conformation of the polymer.The 16-residue long peptide Ace-41 GEWTYDDATKTFTVTE 56 -Nme, as taken out from the full-length GB1 protein NMR structure (PDB: 1GB1 31 ) was modelled using AMBER03-STAR 32,33 forcefield and solvated in a truncated octahedron simulation cell containing 984 TIP3P 34 water molecules and electroneutralized.…”
mentioning
confidence: 99%